Influence of wine-processing on the pharmacokinetics of anthraquinone aglycones and glycosides from rhubarb in hyperlipidemic hamsters. Issue 30 (4th March 2016) - Wang, Min; Hu, Guangnan; Tian, Yuan; Zhang, Zunjian; Song, Rui
Abstract : A high performance liquid chromatography-tandem mass spectrometry method was developed to investigate the influence of wine-processing on pharmacokinetics of anthraquinones from rhubarb in hyperlipidemic hamsters. Abstract : Crude and wine-processed rhubarb products are routinely used as drastic purgative and hypolipidemic agents respectively. To better understand this discrepancy in therapeutic applications, their pharmacokinetics should be investigated. In this study, a reliable high performance liquid chromatography-tandem mass spectrometry method was first developed for the simultaneous determination of anthraquinone aglycones and glycosides from rhubarb in plasma. With satisfactory performance, the developed method was then applied to investigate the pharmacokinetic differences of these anthraquinones after oral administration of crude and wine-processed rhubarb to hyperlipidemic hamsters. The results showed that wine-processing could improve the exposures of emodin, chrysophanol, aloe-emodin, chryphanol-8- O -β-d -glucoside and physcion-8- O -β-d -glucoside, which are considered as hypolipidemic constituents in rhubarb. This is the first attempt to evaluate the effect of wine-processing on the pharmacokinetic behaviors of anthraquinones in rhubarb, and the results could be useful to guide the clinical applications of different rhubarb products and reveal the processing mechanism.